Problematika Penerapan Sanksi Administratif dalam Penertiban Bangunan Liar di Kawasan Perkotaan - Aliya Mardhatilla Az-Zahra; Vanessa Hayla Isyqina; Dewi Ratu Fatima Noviany Sutadi; Aghnia Putri Septiani (Jurnal Hukum dan Sosial Politik, 2025)
The rapid growth of urban areas has triggered the rise of unlicensed development or illegal buildings that have a negative impact on spatial planning, the environment, and the social life of the community. Controlling illegal buildings is a big challenge for local governments, especially in applying administrative sanctions effectively and fairly. This article analyzes various problems faced in applying administrative sanctions, including structural constraints, weak legal culture, and socio-economic impacts of the crackdown. Using normative and empirical juridical approaches, this research evaluates the effectiveness of administrative sanctions in a number of cities such as Surabaya, Bekasi, and Pontianak, and highlights the need for regulatory reform, strengthening the capacity of the apparatus, and participatory approaches to the community. The results show that the effectiveness of administrative sanctions is still limited due to slow bureaucracy, lack of coordination between agencies, and low public legal awareness. Therefore, a comprehensive and collaborative strategy is needed to improve administrative law enforcement that is consistent and has a real impact in creating an orderly, sustainable and socially just urban space.